Trade wars: What do they mean? Why are they happening now? What are the costs?. (4th June 2020) - Mattoo, Aaditya; Staiger, Robert W
SUMMARY: How should economists interpret current trade wars and the recent US trade actions that have initiated them? In this paper, we offer an interpretation of current US trade actions that are at once more charitable and less forgiving than that typically offered by economic commentators. More charitable, because we argue that it is possible to see a logic to these actions: the United States is initiating a change from 'rules-based' to 'power-based' tariff bargaining and is selecting countries with which it runs bilateral trade deficits as the most suitable targets of its bargaining tariffs. Less forgiving, because the main costs of these trade tactics cannot be avoided even if they happen to 'work' and deliver lower tariffs. Rather, we show that the main costs will arise from the use of the tactics themselves and from the damage done by those tactics to the rules-based multilateral trading system and the longer-term interests of the United States and the rest of the world. JEL codes: F02, F13